Inter-Temporal and Cross-Section Variations in Technical Efficiency in the Indian Railways - Raghbendra Jha; Subansh P. Singh (Queen's University, Department of Economics, 1994)
This paper uses recent advances in the theory of measurement of technical efficiency using panel data (Cornwell, Schmidt and Sickles (1990), Jha and Sahni (1992,1993a)) to estimate zone specific technical efficiency in the Indian railways for the period 1966-67 to 1988-89. The analysis covers goods as well as passenger traffic. Apart from providing an in-depth and precise profile of the behavior of technical efficiency in the Indian railways, this analysis provides a framework from which potentially significant policy conclusions can be drawn.
Keywords: 330